Rhinosporidiosis: a clinicopathological study from a Rural Tertiary Health Care Centre, Bihar, India - Majumdar, Aloke Bose; Biswas, Dipayan; Paul, Shib Shankar; Ray, Souradeep; Kumar, Gajendra (International Journal of Advances in Medicine, 2017)
Background: Rhinosporidiosis is a chronic granulomatous infection characterized by a bleeding polypoidal mass which commonly affects the nose and nasopharynx. The disease is caused by Rhinosporidium seeberi. It grows in stagnant water and is thought to be transmitted to human by infected soil and water by gaining entry through traumatized epithelium and mucosa of nose and nasopharynx. It has a high incidence of occurrence among rural population. Surgical excision is the treatment of choice. Methods: Totally, 26 patients of histologically proven cases of rhinosporidiosis were included in this clinicopathological study. The mode of presentation in all these patients was polypoidal nasal mass causing recurrent bleeding and nasal obstruction. The period of study was from May 2010 to April 2014. All patients treated surgically were followed-up from 6 months to 1 year. Results: There were 26 patients of histologically proven rhinosporidiosis of nose and nasopharynx. Of total 26 cases, there were 19 males and 9 female patients in our study with a male to female ratio of 2.7:1. The age of presentation varied from 14 years to 67 years, most patients presenting in the second to sixth decade of life with maximum patients in the third and fourth decade of life and were from rural and poor socio-economic background. Recurrent cases were given dapsone. Conclusion: Rhinosporidiosis which was previously thought to be a fungus is now considered as a protoctista parasite, which involves fish and other amphibians, a fungus like protozoa of the class mesomycetozoea.